Borophene and Graphene for Non-Enzymatic Biosensor- ab-initio study - Ismail, Omar A. (AUC Knowledge Fountain, 2023)
Non-enzymatic glucose sensing holds promise to overcome limitations associated with glucose oxidase, such as oxygen dependence and short shelf life. This study explores the potential sensing capabilities of borophene and graphene through direct interaction with various compounds, including β-glucose, uric acid, ascorbic acid, fructose, and acetaminophen. Using Density Functional Theory (DFT), we calculated binding energies and the respective Density of States (DOS) for these adsorbates on both graphene and borophene surfaces. Preliminary results suggest that borophene might exhibit nearly twice the affinity for β-glucose compared to graphene. Moreover, the calculated Density of States reveals distinct distortions in the electronic states of both graphene and borophene upon β-glucose adsorption. These results suggest unique electronic responses of these two-dimensional materials to glucose adsorption. However, further detailed studies and calculations are crucial for more comprehensive conclusions.